TRANSFORMASI PEMBELAJARAN MENYIMAK CERITA FANTASI: EFEKTIVITAS MEDIA INTERAKTIF EDPUZZLE PADA SISWA SMP - Rahmi Septiana; Hasriani; Abdul Haliq (STKIP Subang, 2026)
This study examines the effectiveness of Edpuzzle media in improving fantasy story listening skills in seventh-grade students at SMP Negeri 22 Makassar. Using a quasi-experimental design with a Nonequivalent Control Group Design, the study involved 40 students divided into an experimental class (using Edpuzzle) and a control class (using YouTube). The results of the independent sample t-test showed a significance value of 0.007 < 0.05, proving a significant difference between the two groups. The posttest average for the experimental class (90.15) was higher than that of the control class (88.15). These findings confirm that Edpuzzle, with its interactive features such as integrated questions and anti-skip, effectively increases students' cognitive engagement and comprehension of oral literary texts. This research provides a practical contribution to the development of digital learning media in Indonesian language education.